Basal elevated serum calcium phosphate product as an independent risk factor for mortality in patients with fractures of the proximal femur—A 20 year observation study. Issue 3 (March 2016) - Kovar, Florian M.; Endler, Georg; Wagner, Oswald F.; Wippel, Andreas; Jaindl, Manuela
Abstract: Introduction: Fractures of the proximal femur are a significant cause of mortality and morbidity in the elderly population. Yet predictive marker of unfavourable prognosis are still lacking. Calcium phosphate product is a marker of osteo-renal dysregulation. This study investigated the role of serum calcium phosphate product (SCPP) levels as a prognostic parameter for outcome in those patients. Patients and methods: A total of 3577 consecutive patients with diagnosed fractures of the proximal femur were included in our study (72.5% females). SCPP was divided into tertiles: <1.92 mmol 2 /l 2, 1.93–2.38 mmol 2 /l 2 and >2.39 mmol 2 /l 2 . Data collection was performed prospectively and statistical evaluation was performed retrospectively. Results: Mean follow up in our study group was 11.0 ± 0.3 months. The mean age of our study group was 79.0 years (SEM ±14 years). To facilitate analysis, patients were divided in two groups: ≤84 years (64.4%) and ≥85 years (35.6%), and mortality <12 months was 12.4% ( n = 445). In our study population higher SCPP levels ad admission were associated with a markedly elevated mortality. In a multivariate logistic regression model adjusted for age and sex, plasma creatinine and haemoglobin at admission caused a 1.3 (CI: 1.01–1.6) for SCPP 1.93–2.38 mmol 2 /l 2, and a 1.6 (CI: 1.2–2.0) for SPP >2.39 mmol 2 /l 2 fold increase in overall mortality compared to patients with baseline SCPP levels (<1.92 mmol 2 /l 2 ) as reference category. Conclusion: Those findings in our study population with 3577 patients over a period of 20 years proved to be, that serum Ca levels may be a good predictor for mortality in patients with fracture of the proximal femur. Further studies are required to evaluate whether these high risk patients might benefit from specific therapeutic measurements. This prognostic factor may help to increase the outcome of elderly patients with a fracture of the proximal femur.